Mental health and social support among Royal Canadian Mounted Police cadets - Nisbet, Jolan; Jamshidi, Laleh; Andrews, Katie L.; Stewart, Sherry H.; Shields, Robyn E.; Teckchandani, Taylor A.; Maguire, Kirby Q.; Carleton, R. Nicholas (Frontiers in Psychology, 2023)
Introduction Certain populations, such as public safety personnel (PSP), experience frequent exposures to potentially psychologically traumatic events and other occupational stressors, increasing their risk for mental health challenges. Social support has been evidenced as a protective factor for mental health. However, research examining perceived social support and its associations with symptoms related to mental disorders among PSP recruits is limited. Methods RCMP cadets (n = 765, 72% male) completed self-report surveys assessing: sociodemographic information, social support, and symptoms related to posttraumatic stress disorder, major depressive disorder, generalized anxiety disorder, social anxiety disorder, panic disorder, and alcohol use disorder. Results The results indicated statistically significant associations between higher social support and decreased odds of positive screens for generalized anxiety disorder, social anxiety disorder, and panic disorder (i.e., significant Adjusted Odds Ratios = 0.90 to 0.95). Discussion Cadets’ perceived levels of social support are comparable to the Canadian general population and higher than serving RCMP. Social support appears to offer a protective element against anxiety-related disorders among participating cadets. Reductions in perceived levels of social support may be a function of RCMP service. Factors contributing to decreased levels of perceived social support should be considered.